Islam Kultural dan Islam Struktural - Aprilia Susilawati; Imam Wijaya Kusuma; Muhammad Nurzen; Agus Rifki Ridwan (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Cultural Islam and structural Islam are two approaches that reflect the dynamics of Islam in society. Cultural Islam Refers to religious expressions that are integrated with local culture, such as traditions, arts and customs. This approach emphasizes harmony between Islamic values ​​and cultural identity, making it more flexible in responding to social change. Meanwhile, structural Islam is more oriented towards systems and institutions, such as politics, economics and law. This approach aims to build a social order that is in accordance with Islamic principles through formal policies and regulations. This research aims to analyze the interaction and contribution of these two approaches in building a balanced life for Muslims between spiritual values ​​and social needs. This study uses a qualitative method with a text analysis approach and in-depth interviews with the main actors in each approach. The research results show that cultural Islam and structural Islam do not conflict with each other, but rather complement each other. Cultural Islam strengthens the spiritual and emotional aspects of society, while structural Islam provides a normative and regulative basis for society's life. In conclusion, integration between cultural Islam and structural Islam can be a solution to face the challenges of modernity without abandoning Islamic values. The synergy between the two is able to create harmony between local traditions and global demands, making Islam an inclusive and relevant religion in various contexts of life.